A novel branch current flow-based construction of microgrids - Kavitha Sivakumar; Jayashree R; Karthikeyan Danasagaran (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
An efficient procedure for defining the boundaries of microgrids in smart distribution systems during distributed generation expansion planning becomes an important consideration in constructing smart grids. A novel approach named "Modified Reverse Current Flow Method" is proposed in this paper to split a large radial distribution system into a required number of self-adequate microgrids. This cluster of microgrids will be capable of utilizing maximum power output of the distributed renewable energy generators and will act as highly reliable zones, during both islanded and grid-connected modes. This method is based on the trend reversal of the flow of current in the various parts of the circuit. This paper uses the practical machine operating curves of the distributed generators to calculate their reactive power output. For the considered distribution system, the proposed method is applied to find the optimal point of operation and the boundaries of microgrids. To bring out the superiority of this novel method, the improvement in reliability indices and economic savings of this method are compared with the results obtained using a similar method available in the literature. This method has several notable merits, namely, increased accuracy in the calculation of annual energy losses and the voltage profile.